Development of Teaching Materials Theme 1 Growth and Development of Living Life in Combinations of Basic Locomotors through Role Playing Activities - Fachrudin Rahmansyah; Nurhasan Nurhasan; Abdul Rachman Syam Tuasikal (BIRCU, 2021)
The purpose of this research is to describe the development of PJOK teaching materials on theme 1 in a combination of basic locomotor movements through role-playing activities, to know learning activities through the development of teaching materials, and to find out the interests of learners through the development of teaching materials. The type in this study uses development. The subjects used in this study were 6 grade III public elementary schools in Sidogedungbatu Village of Sangkapura District of Bawean Islands of Gresik Regency with a total of 89 learners. Instruments in this study use validation sheets, observation sheets of learning activities, and learners' questionnaires. The results and discussion of this research are the development of theme books 1 class III in PJOK material in a combination of basic locomotor movements through role-playing activities is very good, because PJOK learning on theme 1 that uses thematic learning that combines general learning with PJOK learning which is initially less interesting material and still exists that is not in accordance with Basic Competence in the end researchers develop a book of teaching materials in the game. a that can not be separated from the Basic Competencies in the theme book. The results of educator observations there is a percentage of 87% and the results of student observations there is a percentage of 85%. The interest of learners in PJOK teaching material theme 1 growth and development of living things through a combination of basic locomotor motion to role-playing activities in class III there is an overall percentage of 84%. It can be concluded that the development for PJOK teaching materials on Theme 1 is very important because it can be prepared to learners so that learning is more active and interesting.